Magical Allotropes of Carbon: Prospects and Applications. Issue 4 (3rd July 2016) - Tiwari, Santosh K.; Kumar, Vijay; Huczko, Andrzej; Oraon, R.; Adhikari, A. De; Nayak, G. C.
ABSTRACT: The invention of carbon and its allotropes have transformed the electronic and optoelectronic industry due to their encouraging properties in a large spectrum of applications. The interesting characteristic of carbon is its ability to form many allotropes due to its valency. In recent decades, various allotropes and forms of carbon have been invented, including fullerenes, carbon nanotubes (CNTs), and graphene (GR). Since the inception of nanotechnology, carbon allotropes-based nanocomposites have become a leading sector of research and advancement due to their unique bonding properties. Fullerenes and CNTs-based polymer nanocomposites have attracted significant research interest due to their vast applications in every sphere of science and technology. Current research impetus reveals that carbon and its allotropes have revolutionized the industry and academia due to their fascinated properties. Recent advances in various aspects of graphene, CNTs, graphene nanoribbons, fullerenes, carbon encapsulates, and their nanocomposites with polymeric materials and their different applications are reported in this review article. Also, current status and future prospects of graphene-based polymer nanocomposites are presented in common along with proper citations extracted from the scientific literature. Moreover, this article is a unique collection of vital information about GR, CNTs, fullerenes, and graphene-based polymer nanocomposites in a single platform.